Poly(epsilon-caprolactone)nanocapsules as carrier systems for herbicides: Physico-chemical characterization and genotoxicity evaluation - Grillo, Renato [UNESP]; Pereira dos Santos, Nathalia Zocal; Maruyama, Cintia Rodrigues; Rosa, Andre Henrique [UNESP]; de Lima, Renata; Fraceto, Leonardo Fernandes [UNESP] (Elsevier B.V., 2012)
The toxicity of herbicides used in agriculture is influenced by their chemical stability, solubility, bioavailability, photodecomposition, and soil sorption. Possible solutions designed to minimize toxicity include the development of carrier systems able to modify the properties of the compounds and allow their controlled release. Polymeric poly(epsilon-caprolactone) (PCL) nanocapsules containing three triazine herbicides (ametryn, atrazine, and simazine) were prepared and characterized in order to assess their suitability as controlled release systems that could reduce environmental impacts. The association efficiencies of the herbicides in the nanocapsules were better than 84%. Assessment of stability (considering particle diameter, zeta potential, polydispersity, and pH) was conducted over a period of 270 days, and the particles were found to be stable in solution. In vitro release kinetics experiments revealed controlled release of the herbicides from the nanocapsules, governed mainly by relaxation of the polymer chains. Microscopy analyses showed that the nanocapsules were spherical, dense, and without aggregates. In the infrared spectra of the PCL nanocapsules containing herbicides, there were no bands related to the herbicides, indicating that interactions between the compounds had occurred. Genotoxicity tests showed that formulations of nanocapsules containing the herbicides were less toxic than the free herbicides. The results indicate that the use of PCL nanocapsules is a promising technique that could improve the behavior of herbicides in environmental systems. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Environmental chemistry; Triazine herbicides; Polymeric nanoparticles; Sustained release system; Genotoxicity